OVERUSE SYNDROME IN THE RUNNING - Mlan Čoh (University of Banja Luka, Faculty of physical education and sport, 2012)
Walking and running are natural way of human motion. Today running is effective aerobic exercise to maintain vital human functions, mostly cardiovascular and breathing functions. Modern human's lack of movement results in numerous health problems and generally reduce the quality of his life. The impact of regular physical exercise on the body is proven beyond any doubt; but we can also see the growing negative effects of physical exercise, which are typically a result of the unadjusted and to demanding exercise programs. Walking and running are human's the most effective and health activities, but running can have large load on joints, bones, tendons, ligaments and muscular system. The negative effects of physical exercise are manifested in the form of overload which often leads to injuries. Running injuries and their development takes place at the beginning relatively unnoticed, obvious symptoms with pronounce consequences for the runner occur relatively late. Identifying overload factors of the human can help runners and all other athletes who run in their sport disciplines; it is a huge challenge for sports science. Correct and in time answers on overload can have important contribution to a more humane and safe practice.